Pattern Languages: Putting People at the Centre of Design - Sun, Yuchao; Lloyd, Ashley (International Society for Productivity Enhancement, 2005)
First developed for architecture design, pattern languages have been adapted by a number of disciplines, especially software engineering. However these patterns have changed significantly from Alexander's original conception. This paper reports work funded by the UK Economic and Social Research Council's People at the Centre of Communication and Information Technologies programme, which examines some successful and unsuccessful applications of architectural patterns. The results show the essence of Alexander's heory lies in the pattern discovery process, not the patterns per se. This questions the current software pattern approach that predominantly focuses on the prescriptive transfer of technical solutions. Based on Alexander's theory the authors propose a framework for Pattern application that highlights the profound impact on design of adaptation and reflection between human minds and the man-made world. By addressing the flaw of ignoring human instincts in most contemporary design areas it promotes systems that are more human centred and therefore sustainable.